Models for the Design and Operation of Digital Educational Environments - A. V. Solovov; A. A. Menshikova (Высшее образование в России, 2021)
Many educational institutions, assessing their prospects, plan to develop distance educational services using their own electronic and information educational environments (EIEE). During creating and operating EIEE of educational institution (EI), a number of questions arise related to structural, marketing, personnel and other decisions. The purpose of this article is to research the organizational, technical and didactic aspects of the EIEE EI. The methodology of the research is based on methods of system analysis, cybernetics, pedagogical psychology and didacticism.A conceptual model of the EIEE EI as an organizational and technical system has been proposed. It includes a marketing subsystem, a set of technical tools, various types of security and an organizational subsystem. The main functions of these subsystems and their various components have been identified.A didactic model of a typical complex of digital educational resources has been developed. Within this model, the diversity of digital educational resources across each academic discipline is integrated into complexes that provide a complete study at different target levels of assimilation, from initial acquaintance to solving uncharacteristic professionally oriented tasks.From the point of view of pedagogical psychology and cybernetics, the high importance of feedback in EIEE EI is shown. The classification of feedbacks (internal and external) is proposed for the triad “Teacher – Teaching Program – Learner”. The limits of the use of automation in the formation of feedbacks are specified, as opposed to other (non-computer) responses to students’ educational activities. The role and place of feedback in the “digital footprints” of students and teachers is shown and the directions for the use of this data in artificial intelligence systems are outlined.